Reconceptualizing Educational Productivity for Australian Public Schools in New South Wales: An Empirical Application of Modified Quadriform Analytics - R. Anthony Rolle (Educational Considerations, 2016)
Little is known about the educational productivity of public schooling organizations when examined outside of market-based, cost-minimization frameworks. Consequently, the purpose of this research was to extend the literature that supports the appropriateness of measuring levels of the economic efficiency of public schools via an alternative approach, utilizing modified quadriform analytics (MQA) to assess the educational productivity of New South Wales public elementary and secondary schools in Australia over three school years, 2008-2010.
Keywords: Modified Quadriform Analytics; Equality; Educational; Opportunity; Reconceptualizing; public schools; New South Wales; application; emphirical